China and the Asian economies interactive dynamics, synergy and symbiotic growth - Das, Dilip K. 1945- (London Routledge, 2014)
"This book analyzes the emergence of Asian economies, followed by China, as an economic growth pole of enormous significance. Notwithstanding the diversity in the region, rapid growth was instrumental in integrating the Asian economies initially in a market-led manner and this book explores the interactive dynamics and the process of integration in the region".
Emergence of Asia and integration of China -- Launching economic transition in China -- Economic growth in the Chinese economy : an ex-post perspective -- Contemporary state of the Chinese economy and on-going transition to a new growth trajectory -- Evolving pattern of de facto integration between Asia and China -- From market-led to institution-led regional integration in Asia -- Maturing regional economic architecture in Asia.
Includes bibliographical references and index.
Keywords: China -- Foreign economic relations -- Asia; Asia -- Foreign economic relations -- China; China -- Economic conditions -- 21st century; Asia -- Economic conditions -- 21st century; Asia -- Economic integration